1997
DOI: 10.1111/j.1600-0781.1997.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodermatitis from ketoprofen with cross‐reactivity to fenofibrate and benzophenones

Abstract: The aim of this study was to evaluate the possibility of cross-reactivity between ketoprofen, fenofibrate and benzophenones because of their structural similarities. Seven patients presenting photodermatitis from ketoprofen underwent patch and photopatch tests. Ketoprofen, fenofibrate, benzophenone 3, benzophenone 10, benzophenone 4, personal medications and topical creams were tested. All patients had positive patch or photopatch tests to ketoprofen and fenofibrate, four patients had positive UVA photopatch t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Photocontact allergy to ketoprofen seems to induce a number of photo cross-reactions to compounds with structural similarity like benzophenone-3 and the lipid-lowering agent fenofibrate (78,101,102). However, photoallergic reactions to ketoprofen also associate with structurally unrelated compounds like octocrylene (28,84).…”
Section: Topical Nsaidsmentioning
confidence: 94%
“…Photocontact allergy to ketoprofen seems to induce a number of photo cross-reactions to compounds with structural similarity like benzophenone-3 and the lipid-lowering agent fenofibrate (78,101,102). However, photoallergic reactions to ketoprofen also associate with structurally unrelated compounds like octocrylene (28,84).…”
Section: Topical Nsaidsmentioning
confidence: 94%
“…Coz concluded that the photoallergy is due to benzophenone moiety in ketoprofen or to a closely related thiophene-phenylketone part of the tiaprofenic acid rather than their arylpropionic acid function. Sugiura study concluded that the benzoyl radical, not benzophenone is the key structure for the photosensitization of KP suprofen and tiaprofenic acid and their photocrossreactivities [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] this contradiction is due to the limitation of the speculation from the clinical data. Patients had different personal histories using several kinds of drugs.…”
Section: Mechanisms Underlying Sensitization To Kpsmentioning
confidence: 99%
“…1 PPV has traditionally been subdivided into four types (I-IV) according to the type of pigmented lesion accompanying the capillary malformation. 1 PPV has traditionally been subdivided into four types (I-IV) according to the type of pigmented lesion accompanying the capillary malformation.…”
Section: Patient With Extensive Mongolian Spots Nevus Flammeus and Nmentioning
confidence: 99%
“…1 However, this information is not widely known as much as ketoprofen. 1 However, this information is not widely known as much as ketoprofen.…”
mentioning
confidence: 99%
See 1 more Smart Citation